Fluid Flow and Heat Transfer in Cellular Solids - Ettrich, Jörg (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2014)
To determine the characteristics and properties of cellular solids for an application, and to allow a systematic practical use by means of correlations and modelling approaches, we perform experimental investigations and develop numerical methods. In view of coupled multi-physics simulations, we employ the phase-field method. Finally, the applicability is demonstrated exemplarily for open-cell metal foams, providing qualitative and quantitative comparison with experimental data.